2017
DOI: 10.1371/journal.pone.0176090
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal corticosteroids for neonates born before 25 Weeks—A systematic review and meta-analysis

Abstract: BackgroundEfficacy of antenatal corticosteroids before 25 weeks of gestation is unclear.ObjectiveTo assess and compare neonatal outcomes following ANC exposure at 22, 23 and 24 weeks of gestation by conducting systematic review and meta- analysis.MethodsA systematic review of randomised controlled trials (RCT) and non-RCTs reporting on neonatal outcomes after exposure to ANC up to 246 weeks of gestation using the Cochrane systematic review methodology. Databases Pubmed, CINAHL, Embase, Cochrane Central library… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 45 publications
4
17
0
4
Order By: Relevance
“…The methodology including the inclusion and exclusion criteria is similar to our previous review 2. We assessed the composite outcome of death with significant morbidity (eg, severe IVH/PVL, CLD, NEC) in this updated review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology including the inclusion and exclusion criteria is similar to our previous review 2. We assessed the composite outcome of death with significant morbidity (eg, severe IVH/PVL, CLD, NEC) in this updated review.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported a systematic review (eight observational studies, 10 109 neonates) assessing the benefits of ANC at extremely preterm (<25 weeks) gestation 2. ANC exposure was associated with significantly reduced mortality and severe intraventricular haemorrhage (IVH)/periventricular leukomalacia (PVL) in neonates born <25 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published meta-analysis found 8 non-randomized studies on this issue [32]. The impact on neonatal mortality and morbidity of a single dose of corticosteroids administered in the period GW 22 + 0 to GW 23 + 6 is shown in ▶ Tables 4 and 5.…”
Section: 6mentioning
confidence: 99%
“…▶ Table 5 Effects of antenatal steroids on the outcome of infants between GW 23 + 0 and GW 23 + 6 [32]. Consensus-based Recommendation 6.E29…”
Section: Timing Of Antenatal Steroid Administrationmentioning
confidence: 99%
“…Advances in the field of neonatology, i.e. introduction of surfactant therapy 3 and antenatal corticosteroid administration 4 have led to a significant reduction of mortality, especially in developed countries [5][6][7] . Outcomes improve significantly with advancing gestational age, so Bajwa et al found that between 23 and 26 weeks of gestational age (GA), the overall decrease in mortality was 23% for each additional week of GA, yielding a 3% daily decrease in mortality 8 .…”
Section: Introductionmentioning
confidence: 99%